Musserakis sulawesiensis gen. et sp. n. (Nematoda: Heterakidae) collected from Echiothrix centrosa (Rodentia: Muridae), an old endemic rat of Sulawesi, ndonesia - Hasegawa, Hideo; Dewi, Kartika; Asakawa, Mitsuhiko (Zootaxa, 2014)
Musserakis sulawesiensis gen. et sp. n. (Nematoda: Heterakidae) is described from the large-bodied shrew rat, Echiothrix centrosa, one of the old endemic rats of Sulawesi, Indonesia. Musserakis is readily distinguished from other heterakid genera by having non-recurrent and non-anastomosing cephalic cordons, by lacking papillae between papillae groups around precloacal sucker and cloacal aperture and by lacking teeth in the pharyngeal portion. The spicules are equal but with marked dimorphism among individuals. Heterakids collected from other old endemic murids examined, i.e., Crunomys celebensis, Tateomys macrocercus and Tateomys rhinogradoides, and the new endemic rats of Sulawesi, were Heterakis spumosa Schneider, 1866, a cosmopolitan nematode of various murids. It is suggested that M. sulawesiensis is specific to Echiothrix.